Concentración de Inmunoglobulinas de calostro bovino utilizando tecnología de membranas - Páez Fiallos, Ana Lucía (2015)
The work was concentrated bovine colostrum immunoglobulins to which livestock breed selection held at the canton of Cayambe is chose three farms and four cows took samples of bovine colostrum from first to sixth milking, analysis was performed physico-chemical in which composition, density and acidity was determined. Through the colostrometer determined the con centration of immunoglobulins also microbiological analysis of bovine colostrum by equipment that uses flow cytometry analysis. To determine the kinetics of decrease was managed team of high resolution HPLC with gradient Elution liquid chromatography using as pattern plasma blood cattle. The process of membrane technology was micro-filtration to concentrate by varying temperature and pressure parameters, analysis of coliforms and Echerichia coli, also to check the concentration after the microfiltration process was analyzed the area by HPLC. Two-way ANOVA statistical test was applied to measure the variation in the concentration of bovine colostrum immunoglobulins. Chemical physical analysis yielded maximum values of total 14, lactose 7.6, solid total 39.1, solid non fat 24.8 16.9, fat protein, density of 1,115 gmL and titratable acidity of 42.67 ° Dornic; It was determined the most representative peak with maximum area of 98997186, in a time of 1,3805 mean retention. Bovine colostrum immunoglobulin concentrate is independent of the process applied to the concentration by membrane technology.